In vitro evaluation of lactic acid bacteria with probiotic activity isolated from local pickled leaf mustard from Wuwei in Anhui as substitutes for chemical synthetic additives - Wu Changjun (De Gruyter, 2021)
The extensive abuse of chemical synthetic additives has raised increased attention to food safety. As substitutes, probiotics play an important role in human health as they balance the intestinal microbes in host. This study was aimed to isolate and evaluate the potential probiotic activities of lactic acid bacteria (LAB) from a local pickled leaf mustard (PLM) from Wuwei city in Anhui province through in vitro experiments. A total of 17 LAB strains were obtained as probiotics. All the isolates were sensitive to chloramphenicol, tetracycline, erythromycin, and doxycycline but exhibited resistance to antibiotics (e.g., streptomycin, kanamycin, gentamicin, and vancomycin). Out of the 17 strains, 9 were sensitive to most of the antibiotics and had no cytotoxic activity on human colorectal adenocarcinoma cell line (HT-29) cells. The isolated AWP4 exhibited antibacterial activity against four indicator pathogen strains (ATCC8099: Escherichia coli, ATCC6538: Staphylococcus aureus, ATCC9120: Salmonella enteric, and BNCC192105: Shigella sonnei). Based on the phylogenetic analysis of the 16S rRNA gene, AWP4 belonged to Lactiplantibacillus plantarum. This study indicated that the Wuwei local PLM could be a potential resource to isolate beneficial LAB as probiotics. The data provide theoretical guidance for further animal experiments to estimate the probiotic effect and safety of Lpb. plantarum AWP4 in vivo.